The woodlouse (Isopoda: Oniscidea) fauna of steppe habitats in the Kostanay region of Kazakhstan - Bragina, Tatyana M.; Khisametdinova, Dilyara D. (Hacquetia, 2018)
This paper presents first materials on the fauna and distribution of the terrestrial isopods - woodlice (Oniscidea) inhabiting the central and southern parts of Kostanay Region (Kazakhstan, Northern and Southern Turgai), located in the steppe zone. Most of the specimens of woodlice were collected in the territory of the National Nature Reserve “Altyn Dala”, a new protected area (established in 2012) and in the area of the Naurzum National Nature Reserve (established in 1931, World Heritage Site of UNESCO), on the Stipa lessingiana dry steppe. The list of woodlice includes six species (Crustacea: Isopoda: Oniscidea), belonging to five genera and three families in the study area. Four species are recorded for the first time in Kazakhstan - Desertoniscus subterraneus Verhoeﬀ, 1930, Parcylisticus dentifrons (Budde-Lund 1885), Porcellio scaber Latreille, 1804, and Protracheoniscus major (Dollfus 1903). Distribution characteristics are provided for all of those species recorded in the study area. For the territory of Kazakhstan, according to a literature data, currently 16 species of terrestrial isopods have been recorded.